Lecturer Competency Development Based on Continuous Professional Development using Borg & Gall and ADDIE Model - Jenni Ria Rajagukguk (JETL (Journal of Education, Teaching and Learning), 2025)
As educators and researchers, lecturers do not merely serve as conveyors of knowledge, but also as learning facilitators, innovators, and student mentors. Advances in science and technology, along with the increasingly dynamic demands of the workforce, require lecturers to continuously develop their competencies in a systematic and sustainable manner. The challenges faced in the era of globalization include rapid access to information and the digital technology revolution, as well as the need for graduates who are adaptable, creative, and competitive in the global market. Therefore, it is essential to continuously update their knowledge and academic competencies to keep pace with advancements in science and technology. Similarly, this applies to the curriculum, regulations, and standards of higher education; the need for faculty career development; and the strengthening of universities’ roles in society as knowledge brokers. Professionally competent and continuously developing faculty members strengthen their capacity to solve problems and collaborate with stakeholders. The research question is: What are the competencies of faculty members in professional development that is sustainable? The research objective is to determine the competencies of faculty members based on professional development that is sustainable, with a 90% success rate based on the BKD report each semester. Research methods: the Borg & Gall model and the ADDIE model